Application of genetic algorithm to solving the optimization problem of locations graph vertices in the line - Liubomir Chiriac; Natalia Lupashco; Maria Pavel (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
This article examines genetic algorithms that are built on the "survival of the fittest" principle enunciated by Charles Darwin. By applying genetic algorithms to solving optimization problems, it is not always possible to guarantee the determination of the global optimum in polynomial time. This fact does not occur because only brute force search methods allow us to find the global optimum. Instead the genetic algorithm allows selecting good decisions, in a reasonable time, compared to other well-known deterministic or heuristic search engine optimization algorithms. The authors of this article develop an algorithm of solving the optimization problem of locations graph vertices in the line.